ЕЛЕКТРОМАГНІТНІ ПАРАМЕТРИ ІНДУКТОРА ДЛЯ ЗБУДЖЕННЯ ІМПУЛЬСІВ СТРУМУ В ПРОЦЕСАХ ЕЛЕКТРОПЛАСТИЧНОЇ ДЕФОРМАЦІЇ МЕТАЛІВ - Ращепкін, А.П. (Інститут електродинаміки Національної академії наук України, 2019)
With reference to the use of the electroplastic effect in special methods of plastic deformation, based on the additional effect of high-density current on the material, an induction method has been developed for the excitation of high-density current pulses in a processed metal. The electrical parameters of the inductor were determined by computer simulation using the finite element method. With respect to technological processes with continuous, repeated repetition of pulses, in order to avoid overheating, the multi-turn winding of the end cylindrical inductor is performed by a water-cooled coil made of a hollow rectangular copper wire. Excitation of a unipolar current pulse was carried out by discharging a capacitor using a controlled thermistor to an inductor. No stationary electromagnetic processes of discharge in the circuit are considered using the known dependences in theoretical electrical engineering, and the distribution of the current density in the metal by the finite element method. References 15, figures 5.